Evaluasi Usability pada Aplikasi Mobile GOBIS Suroboyo Bus dengan Metode Usability Testing - Yulie Fauzanah; Aditya Rachmadi; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
GOBIS Suroboyo Bus is an application developed by Dinas Perhubungan Surabaya to monitor Bus movements in real time and to know the distance between stops. Based on the findings on the Playstore there are user complaints that affect the usefulness of such applications, the GOBIS application does not provide the clock information or the arrival time of the bus, not according to the position of the bus on the application by the field, To get stop information and travel routes users need to zoom-in so it takes a while. Therefore, the usability test is done to get a deepening problem regarding usability and measuring the user's ease of access to an application. To test the usability of GOBIS application is done 2 times to five aspects, namely learnability, efficiency, memorability, error, and satisfaction using questionnaires. Achieved usability test results on the learnability aspect of 1.28 from the first and second Test comparisons. Efficiency aspect of 63.77%. The memorability aspect is experiencing improvements in the capabilities of the number of clicks and step counts. For satisfaction aspect obtained 65.25% from SUS questionnaire results.